PROTOTIPE ALAT EVAPORATOR VAKUM (EFEKTIVITAS TEMPERATUR DAN WAKTU EVAPORASI TERHADAP TEKANAN VAKUM DAN LAJU EVAPORASI PADA PEMBUATAN SIRUP BUAH MENGKUDU (Morinda citrifolia L.)) - Syakdani, Adi (Politeknik Negeri Sriwijaya, 2019)
The prototype of vacuum evaporator unit has a purpose to reduce moisture content of juice by using the minimum temperature at vacuum condition so that the nutritional value of the obtained product will not be vanished. An encountered problem in processing the food products is how to reduce the moisture content. By reducing moisture content, it is able to raise the shelf life of products, avoid the detrimental effect to the unit, and increase the economic value. The syrup is made with the evaporation process at the pressure below the atmospheric pressure subsequently the boiling point of the solvent is decreased. The evaporation process uses vacuum evaporator is done by setting the set point of process control which are the evaporating temperature 50 and 60ËšC within the time of 10, 20, 30, 40, and 50 minutes. The analyzed result shows that the optimum evaporation rate is 0.953 gr vapors/mins with the moisture content of 56.88% at 60ËšC. The operating pressure of this unit is 19 cmHg. In this operating pressure, the boiling point of water is descending so that the evaporation process is safe for the feed which is sensitive to the heat.